Pementasan Dramatari Calonarang Wirada Sungsang Sebagai Media Penerangan Agama Hindu Di Pura Dalem Desa Pakraman Batuyang, Gianyar - Ni Wayan Eka Sumartini; Dewa Ketut Wisnawa; I Wayan Suwadnyana (Jayapangus Press, 2019)
Research on the performance of the Calonarang drama was deemed still essential enough to be traced through scientific research activities, given the incompatibility between understanding and its application in religious life. This indication can be seen from the existence of religious activities that have not led to understanding and meaning in harmony with Hindu literature. This is the obstacle in transforming the values ​​of Hinduism contained in the performance of the Calonarang drama.The performance of the Calonarang drama is very closely related to the worship of God Almighty, so that he is pleased to go down to the world (napak pertiwi) and give waranugraha, prosperity to the damuh (human) and nature. The Wirada Sungsang play has the main uniqueness in the performance of Calonarang in general, the form between Walunateng Dirah and Wirada Sungsang is almost the same which distinguishes the gelat used The results of this study suggested that: Changes in the play did not change the essence of the function and philosophical meaning of the purpose of the Calonarang drama performance, namely offering to God Almighty, 2) The function of education should be considered, where it is hoped that through the performance the audience can benefit or miser from the figures who play a role in the play. The hope of researchers is that the pragina (dancers) have religious knowledge, namely tattwa, morality, and events, so that later when the performance takes place there is a transfer of religious values ​​in the form of communication between actors and spectators, 3) Belief in the power of two / two litas it will further define our actions for the preservation of nature so that the concept of Tri Hita Karana can be realized, carried out by worshiping Mother Earth and akasa (MahaIFather